Marsh marigolds growing by a stream at Prestvannet ... - Campbell, Sandy (University of Alberta Library, 2024)
The area around Prestvannet Lake in Tromsø, Norway is boggy. There are several small streams feeding into the lake. Marsh marigolds grow along the streams. ...